Upstream SLC2A1 translation initiation causes GLUT1 deficiency syndrome - Willemsen, Michèl A (Eur J Hum Genet, 2017)
Glucose transporter type 1 deficiency syndrome (GLUT1DS) is a neurometabolic disorder with a complex phenotypic spectrum but simple biomarkers in cerebrospinal fluid. The disorder is caused by impaired glucose transport into the brain resulting from variants in SCL2A1. In 10% of GLUT1DS patients, a genetic diagnosis can not be made. Using whole-genome sequencing, we identified a de novo 5′-UTR variant in SLC2A1, generating a novel translation initiation codon, severely compromising SLC2A1 function. This finding expands our understanding of the disease mechanisms underlying GLUT1DS and encourages further in-depth analysis of SLC2A1 non-coding regions in patients without variants in the coding region.